Nematocytes in the Coral Species Acropora formosa on Kasiak Island, Pariaman City, West Sumatera - Pratama, Bima; Thamrin, Thamrin; Nursyirwani, Nursyirwani (Journal of Coastal and Ocean Sciences, 2025)
This research was conducted in January 2024 on Kasiak Island, Pariaman City, West Sumatra Province. This research aims to identify nematocytes found in the body tissue of the Acropora formosa coral. The method used in this research is a survey method with direct observation and sampling in the field. Determination of the type of nematocytes from A. formosa coral was carried out using an Olympus microscope with an objective lens magnification of 10X40 (400) at the Marine Biology Laboratory, Faculty of Fisheries and Marine, Universitas Riau. Of the 25 main types of nematocytes known in the phylum Cnidaria, one type was found in this species. The results of the research show that there is a type of Holotrichous isohiza in the A. formosa coral. This type of nematocyte is thought to be used to attack and kill prey